Sexual Behavior in Adolescent Courtship, Exposure to Pornography, and Parental Sexual Communication - Lestari, Sri (Faculty of Psychology, Universitas Surabaya, 2010)
The aim of this study was to find out the correlation between parent–child communication about sexuality and exposure to pornography with adolescent’s sexual behavior in courtship. Participants were 551 adolescents (225 boys and 326 girls) who lived at Sukoharjo. Results show a correlation between parent–child communication about sexuality and Internet exposure to pornography and sexual behavior in dating. Implications of this study are discussed. Penelitian ini bertujuan mengetahui korelasi komunikasi orangtua-anak tentang seksualitas dan paparan pornografi dan perilaku seksual remaja dalam berpacaran.Partisipan penelitian ini adalah 551 remaja (225 laki-laki; 326 perempuan) yang tinggal di Sukoharjo.Hasil penelitian menunjukkan bahwa ada korelasi perilaku seksual dalam berpacaran dan komunikasi orang tua-anak tentang seksualitas dan paparan pornografi.Dibahas pula implikasi temuan ini.